Fault detection and prognostic of abnormal equipment situations using wavelet decomposition technique - Ling, Wee Kee (2011)
Unplanned system failure results in high cost and liabilities for system operators. The implementation of effective prognostics systems would allow identification of faults before the actual occurrence of critical failure thereby avoiding and mitigating system failures. This project focuses on identifying fault characteristics of Marathon Electric AC Induction motor. Broken Rotor Bar, Motor Bearing and Rotor Unbalance Faults would be presented in detail.